2022
DOI: 10.1007/978-3-030-96977-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the COVID-19 Pandemic: A Qualitative Study of Government Policies Relating to the Early Childhood Sector Across Ten Countries

Abstract: translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…A review of the literature showed that there were very few studies that included teachers from different countries. In studies that included a multi-country sample, the purpose differed from that of the present study, For example, the study by Anderson et al (2022) focused on parental engagement and perspectives on distance learning and the study by Rothe et al (2022) compared early childhood policies in different countries. These studies also adopted different research designs.…”
Section: Strengths Limitations and Recommendations For Future Researchmentioning
confidence: 99%
“…A review of the literature showed that there were very few studies that included teachers from different countries. In studies that included a multi-country sample, the purpose differed from that of the present study, For example, the study by Anderson et al (2022) focused on parental engagement and perspectives on distance learning and the study by Rothe et al (2022) compared early childhood policies in different countries. These studies also adopted different research designs.…”
Section: Strengths Limitations and Recommendations For Future Researchmentioning
confidence: 99%